种含钒石煤水蒸汽炭化预处理制备V2O5的方法 (2017)
本发明专利涉及种含钒石煤水蒸汽炭化预处理制备VO的方法。其技术方案是：先将含钒石煤原料用球磨机粉碎至100～200目，将所述矿粉与浓硫酸按质量比1：（0.2～0.4）搅拌均匀，再在上述混合物中加入8～15%的0.5～5g/L引发剂溶液，搅拌20～30 min。搅拌后的湿砂状混合物，用传输带装入料斗车中，然后推入水蒸汽炭化室中在150～250℃进行炭化。炭化渣以固液比为1：（1～2），进行二段法浸取钒，滤液为蓝色的溶液，然后按照常规湿法冶金制备VO的方法，便可以得到99.5%以上的五氧化二钒产品。本发明无矿石焙烧过程、不产生废气，工艺简单、易大规模化生产，钒的浸出率能大大提高。 The invention relates to a preparation method of V2O5 by vapour carbonizing pretreatment of vanadium-containing stone coal. The technical scheme comprises steps of smashing a vanadium-containing stone coal raw material to 100-200 meshes by a ball mill; mixing the mineral powder and concentrated sulfuric acid evenly in the ratio of 1: (0.2-0.4), and then adding 8-15% of 0.5-5 g/L of initiator solution in the mixture, and stirring for 20-30 min. A wet sand shaped mixture after stirring is loaded to a hopper truck through a conveying belt, and then pushed to a vapor carbonizing room to carbonize at 150-250 DEG C. The carbonized slag is performed with a two-stage process to leach vanadium according to the solid-to-liquid ratio